Outcome of Missed Monteggia Lesions in Children Managed by UlnarOsteotomy & Open Reduction of Radial Head (The Planet, 2024)
Introduction: Missed Monteggia lesions in children require prompt management to avoid complications. This study evaluated outcomes of children treated with ulnar osteotomy and radial head open reduction at a tertiary hospital in Bangladesh. Methods & Materials: This prospective observational study was carried out from July 2017 to June 2019 at the Department of Orthopedics, National Institute of Traumatology and Orthopedic Rehabilitation (NITOR), Dhaka, Bangladesh. This study evaluated outcomes in 16 pediatric patients (ages 4–15) with missed Monteggia lesions. Participants were selected via purposive sampling based on inclusion criteria. After pre-operative evaluation, surgical intervention was performed, and follow-ups assessed pain, range of motion, and Mayo Elbow Performance Score (MEPS). Data were analyzed using SPSS 25. Result: The mean age of participants was 9.81 years, with a male predominance (68.75%). Falls from height were the most common injury mechanism (75.00%), predominantly affecting the left side (56.25%). The mean duration from injury to operation was 8.06 months. Post-operatively, pain levels decreased significantly, with 31.25% reporting no pain and 68.75% reporting mild pain. Range of motion improved, with a decrease in the pronation-supination arc and an increase in the flexion-extension arc. MEPS scores showed substantial enhancement from a mean of 62.50 to 80.94. A significant association was observed between the duration from injury to operation and final treatment outcome. Conclusion: Ulnar osteotomy and radial head open reduction effectively relieved pain, restored elbow function, and improved outcomes in children with missed Monteggia lesions, highlighting the importance of timely intervention.
Keywords: Missed Monteggia Lesions; Ulnar Osteotomy; Open Reduction; Radial Head; Pediatric Orthopedics